2003
DOI: 10.1046/j.1360-0443.2003.00524.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of oral selegiline plus nicotine skin patch compared with placebo plus nicotine skin patch for smoking cessation

Abstract: Adding selegiline to nicotine patch was associated with a doubling of the 52-week continuous abstinence rate, but this difference was not statistically significant. Selegiline significantly reduced craving for cigarettes and appeared to mitigate the need for nicotine replacement therapy. The results suggest that selegiline is a promising drug for future smoking cessation research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 9 publications
1
36
0
Order By: Relevance
“…These data were not repro-duced when investigated in a larger patient cohort where no improvement over placebo was observed (Weinberger et al, 2010). Similarly, a study with 108 participants in Israel also failed to demonstrate superiority over placebo (Biberman, Neumann, Katzir, & Gerber, 2003). A transdermal patch of selegiline in combination with cognitive behaviour training treating 243 adult smokers also did not show a statistical difference to placebo (Killen et al, 2010).…”
Section: Smokingmentioning
confidence: 84%
“…These data were not repro-duced when investigated in a larger patient cohort where no improvement over placebo was observed (Weinberger et al, 2010). Similarly, a study with 108 participants in Israel also failed to demonstrate superiority over placebo (Biberman, Neumann, Katzir, & Gerber, 2003). A transdermal patch of selegiline in combination with cognitive behaviour training treating 243 adult smokers also did not show a statistical difference to placebo (Killen et al, 2010).…”
Section: Smokingmentioning
confidence: 84%
“…htm). Previous studies demonstrated that selegiline was an effective aide in smoking cessation (Biberman et al, 2003;George et al, 2003). At least four clinical trials are currently underway to evaluate the effectiveness of selegiline as a potential therapy in smoking cessation (http://www.…”
Section: Discussionmentioning
confidence: 99%
“…oral selegiline increased the trial endpoint (8-week) 7-day point prevalent abstinence compared with placebo by 3-fold (George et al, 2003). In a third study that used a combination of oral selegiline and nicotine patch, selegiline plus nicotine patch doubled the 52-week continuous abstinence rate compared with nicotine patch alone, although the difference was not significant due to small subject numbers (Biberman et al, 2003). Other MAO inhibitors have also been investigated for their effects on smoking cessation, but due to poor efficacy (moclobemide) or toxicity (lazabemide), they are no longer studied (McRobbie et al, 2005).…”
mentioning
confidence: 99%
“…[7][8][9][10]12 In our selegiline clinical trial, overall the drug had no effect on any of the primary outcome measures. 11 However, the present pharmacogenetic analysis of the same clinical dataset revealed several significant results.…”
Section: Discussionmentioning
confidence: 99%
“…8 A randomized double-blind placebo-controlled trial of oral selegiline plus NRT in 109 smokers reported an association between selegiline and reduced craving. 9 In contrast, another study of comparable design and similar size showed no effect of oral selegiline on craving or abstinence. 10 We recently performed the first trial of transdermal selegiline for smoking cessation.…”
Section: Introductionmentioning
confidence: 94%